Blackwell Publishing Ltd Has urbanization become a risk factor for dental caries in Kerala, India: a cross-sectional study of children aged 6 and 12 years - BRADLEY CHRISTIAN & R. WENDELL EVANS (International Journal of Paediatric Dentistry 2009, 2009)
Objectives. The objectives of this study were to: (i) test the hypothesis that urbanization is a risk factor for dental caries in children aged 6 and 12 years in Kollam, Kerala; and (ii) identify other possible risk factors for dental caries. Methods. A cross-sectional study design was followed. The subjects were stratified by socio-demographic status into urban middle class, urban poor, and rural poor. Caries experience was measured byvisual examination of teeth according to the World Health Organization criteria. Data on potential risk factors were collected using a close-ended, structured, and interviewer-administered questionnaire. Data modelling was conducted using logistic regression analyses Results. Eight hundred seventy-six children were examined; 53 per cent of 6-year-olds and 90 per cent of 12-year-olds examined were caries free. The caries experience rates were 1.40 decayed, missing, or filled primary teeth and 0.15 Decayed, Missing, and Filled Teeth (DMFT) for the 6- and 12-year-olds, respectively. Urban children did not have a higher caries experience compared with rural children.The only risk factor associated with a significant difference in DMFT scores was the dental visiting pattern. Children who visited the dentist had a significantly higher mean DMFT score (P = 0.009). Conclusion. There was no evidence that urbanization is a risk factor for dental caries in Kerala. Dental caries experience was low, against any standard, in Kollam. Risk factors for caries were not identified.